Studi Analisis Pengelolaan Praktikum Keagamaan Islam Perspektif Kurikulum - Kisbiyanto, Kisbiyanto (THUFULA, 2013)
Abstract: This study used a qualitative approach, to describe the (1) curriculumpolicy planning charged practices in Islamic learning, (2) form of charged practice curriculum in the learning of Islam, (3) curriculum implementation and evaluation in Islamic learning. Research results: (1) There are 63 subjects containing 155 credits in Islamic Religious Education at Tarbiyah Department of Kudus Islamic State College of Islam have clearly been prepared their practicums, at least there are eight practicums, including: Arabic, English, worship, information and technology, research, profession/micro teaching, field professional practicums, and real practice (KKN). The eighth subjects arenamed practicum courses, (2) in addition, there are 20charged forms of the practice course, 24 other regular subjects, but have a lab charge, and of the twenty- four, decent into practicum courses are statistics, both descriptive and inferential, (3) the implementation of learning to eight practicum courses, offered in sequence from the first half to eight semesters, charged by evaluating the curriculum refers to the practice of learning and evaluation system. Passing valuation of each subject is specified minimum value of 2.00, except Field Professional Practice (PPL) that must reach a minimum value of 3.49 .